1999
DOI: 10.1111/j.1572-0241.1999.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Des-Gamma-Carboxy Prothrombin Levels Determined by A New Generation of Sensitive Immunoassays in Patients With Small-Sized Hepatocellular Carcinoma

Abstract: Compared with the conventional method, the sensitivity in detecting small-sized HCC was increased in the two new DCP immunoassays (ECLIA and IRMA). The overall performance as evaluated by an ROC analysis was significantly better in ECLIA than in IRMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of PIVKAII in the diagnosis of patients with HCC had been about 55% using a conventional kit (EI-test mono-P-II kit, Eisai Laboratory) before 1998. Several studies on the contrasting sensitivity kit and the conventional kit confirmed that the new kit is more sensitive than the conventional one in diagnosing HCC patients after 1998 (Mita et al, 1998;Nomura et al, 1999). The sensitivity is about 65% in patients diagnosed with HCC (Mita et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the level of AFP is elevated in patients with both HCC and chronic liver disease; thus, there is wide overlapping between the two groups [144,145]. Most studies adopt a cutoff value of 20 ng/mL for AFP, with a sensitivity ranging from 49 to 71% and specificity from 49 to 86% in HCCs smaller than 5 cm [146][147][148][149][150][151][152][153][154]. Limitations in the sensitivity and specificity of AFP in surveillance of high-risk populations have led to the use of US as an additional method for the detection of HCC [142,[155][156][157].…”
Section: What Modality Should Be Used?mentioning
confidence: 99%